Recent advances in solvers for nonlinear alegebraic equations - Dent, Deborah; Paprzycki, Marcin; Kucaba-Piętal, Anna (Computer Assisted Methods in Engineering and Science, 2023)
In this paper the performance of four solvers for systems of nonlinear algebraic equations applied to a number of test problems with up to 250 equations is discussed. These problems have been collected from research papers and from the Internet and are often recognized as "standard" tests. Solver quality is assessed by studying their convergence and sensitivity to simple starting vectors. Experimental data is also used to categorize the test problems themselves. Future research directions are summarized.